Collaboration between stakeholders in the design of a context-based curriculum in Ghana - Hannah Edjah; Eugene Adu Henaku; Abraham Kwadwo Okrah; Nozomi Sakata; Chris Yates (Journal of International Cooperation in Education)
Purpose – This study examines the nature and forms of collaboration among stakeholders that led to and existed during the design of the B.Ed. curriculum for the Colleges of Education (CoE) in Ghana. It aims to highlight the views of local stakeholders about the processes in an educational project that were likely to have enhanced the importance of contextualisation in the curriculum change process. The paper also prioritises the voices and views of local stakeholders, which have often been stifled in the process of curriculum change in Ghana. Design/methodology/approach – A qualitative approach, using semi-structured interviews, was used to collect data from 17 local stakeholders. Thematic analysis and social constructivism framed the interpretation of findings. Findings – The study found that the CoE reform prioritised local stakeholders’ input throughout a highly collaborative process. This collaboration unexpectedly led to the development of a curriculum reflective of the Ghanaian context. However, ideological conflicts emerged at both the international and local levels, particularly regarding approaches to change and the decision to extend CoE management to four public universities. The conflicts underscore the power dynamics inherent in educational reforms funded by foreign aid. Originality/value – The research offers crucial insights for policymakers and curriculum developers regarding the importance of local stakeholder engagement in collaborative reforms involving foreign aid. The study underscores the need for active involvement from all stakeholders to create contextually relevant curricula. While conflicts may arise, the research highlights that a social constructivist approach, combined with continuous communication, negotiation and compromise, can lead to meaningful and sustainable curriculum reform outcomes.